2020
DOI: 10.24127/ajpm.v9i4.3172
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Lembar Kerja Peserta Didik (Lkpd) Berbasis Higher Order Thinking Skill (Hots)

Abstract: Tujuan penelitian ini adalah untuk mengembangkan lembar kerja peserta didik (LKPD) berbasis higher order thinking skill (HOTS) yang dapat memfasilitasi siswa dalam melatih kemampuan berpikir tingkat tingginya. Metode penelitian yang digunakan merupakan penelitian dan pengembangan. Proses pengembangan LKPD diadaptasi dari model pengembangan 4-D (Four-D Models) yang terdiri dari pendefinisian (define), perancangan (design), pengembangan (develop), dan penyebaran (disseminate). Tahap pendefinisian meliputi analis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 1 publication
1
6
0
6
Order By: Relevance
“…The results showed that applying the discovery learning model, assisted by electronic worksheets based on Google Docs, improved students' HOTS abilities. This finding is consistent with the results of studies conducted by Purwasi and Fitriyana (2020), Sari and Pradita (2018), and also Kholid Yusuf (2018). This increase is due to the discovery learning steps that facilitate students to develop their HOTS abilities.…”
Section: Stopping Cyclesupporting
confidence: 93%
“…The results showed that applying the discovery learning model, assisted by electronic worksheets based on Google Docs, improved students' HOTS abilities. This finding is consistent with the results of studies conducted by Purwasi and Fitriyana (2020), Sari and Pradita (2018), and also Kholid Yusuf (2018). This increase is due to the discovery learning steps that facilitate students to develop their HOTS abilities.…”
Section: Stopping Cyclesupporting
confidence: 93%
“…Through problem-based student worksheets, students are able to think complexly in solving material, draw conclusions, analyze and build relationships by involving the most basic mental activities (Nadifatinisa & Sari, 2019;Noprinda & Soleh, 2019). Problem-based student worksheets can also facilitate students in practicing higher-order thinking skills (Muzayyanah et al, 2020;Purwasi & Fitriyana, 2020).…”
Section: Practitioner Validation Resultsmentioning
confidence: 99%
“…(Khotimah, 2020) baru-baru ini melakukan penelitian terkait pengembangan lembar kerja peserta didik dalam konteks lingkungan, berbasis Higher Order Thinking Skills (HOTS) yang bertujuan untuk mengembangkan lembar kerja siswa dan menguji kevalidan dan kepraktisannya. Juga penelitian dari (Purwasi, Lucy Asri dan Fitriyana, 2020). Yang bertujuan untuk mengembangkan lembar kerja peserta didik (LKPD) berbasis HOTS untuk menfasilitasi kemampuan dan peningkatan berfikir siswa pada tingkat yang lebih tinggi.…”
Section: Menggunakan Metodeunclassified